Pathological Manifestations of the Iris in Primary Chronic Open-Angle Glaucoma: Pathological Manifestations of the Iris - Nassiri, Nader; Shahriari , Mansoor; Delavari , Zahra Sadaat; Porkar Rezaeyeh, Arvin; Kavousnezhad , Sara; Sheibani , Kourosh (Journal of Ophthalmic and Optometric Sciences, 2023)
Purpose: This study aims to assess the histopathological changes in the iris of patients diagnosed with primary chronic open-angle glaucoma (PCOAG) undergoing trabeculectomy surgery. Patients and Methods: Conducted at the Imam Hossein Medical Center in Tehran, Iran, this study included 25 patients diagnosed with PCOAG scheduled for trabeculectomy. Exclusion criteria included patients with diabetes mellitus, systemic hypertension, uveitis, vascular lesions, central retinal vein occlusion, pseudoexfoliation, iris neovascularization, and previous prostaglandin usage. Following peripheral iridectomy, iris specimens were fixed in 10 % formalin, processed, and stained with hematoxylin and eosin for histopathological examination. The evaluation focused on vascular hyalinization, anterior border layer (ABL) thickness, stromal pigmentation, and pigmented epithelium characteristics. Results: Twenty-five patients (mean age 64.4 ± 8.8 years) participated in the study. Notable findings included vascular hyalinization in 72 % of patients, ABL thickening in 48 %, severe stromal pigmentation in 40 %, and vacuolated or depigmented epithelium in 32 % and 4 % of patients, respectively. Intranuclear inclusions and nuclear invaginations were noted in 88 % of cases. The average number of glaucoma medications used per patient was 1.3 ± 1.1.Z Conclusion: The present study results underscore the significant histopathological alterations in the iris in PCOAG patients. These changes are likely influenced by factors such as aging, patient ethnicity, and increased intraocular pressure. Gaining a deeper understanding of these changes is vital for advancing PCOAG management and treatment methodologies.